SILENCE – AN UNHEARD FACE OF LAYAM - U., Bhavani; S, Subbulakshmi (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Rhythm is an integral part of the universe. Every aspect of nature works in a pattern or cycle. This innate natural rhythm is called Layam. When this layam gets disrupted, it becomes Pralayam, Disaster. It is an equally important aspect in the Art forms like Music or Dance. According to the Indian Music system, the layam is the natural tempo, while Tala is considered the tool to measure the layam for the length of a specific composition. The concept of Tala Dasa Pranas describes the Ten lifelines of the Tala for any composition. As per that, Laya is the space or the rest between the two actions. This space can either be filled with sounds or silence. The aesthetics lie in understanding the appropriate usage of sounds and silence concerning proportion, place, and reason. Silence intensifies an emotion, letting one experience it for longer without any distraction or change. The placement of silence in different contexts might convey different meanings or emotions. Silence, due to lack of words or sounds, gives an individual the freedom of interpretation and imagination. Apart from music or dance, phrases like ‘awe struck’ or ‘dumb struck’ denote one’s loss of words during an emotionally heightened situation. In this study, Silence, an important aspect of layam, has been studied concerning literature, Music, Jathi recitation, Nritta of the dance and the emotional expression or Abhinaya of dance. This study enables a better understanding of the importance and power of silence, an aspect of Layam.